Who’s Active Actor? The Analysis of Moderating Impact of Opportunity and Cost on Personal Energy Saving Behavior and Public Policy Participation - Jeon, Sehyeok; Kim, Seoyong; Kim, Miri (Journal of Sustainability Research, 2024)
Background: In order to combat climate change, research into the drivers of energy saving is critical. The aim of this study is to analyze the effects of value factors and theory of planned behavior factors on energy saving behavior and policy participation in terms of moderating effects of opportunity and cost. Methods: The data was collected in 2022 through the “National Opinion Survey on Energy” by the Center for Energy Transition Policy Research under Social Science Research Institute, Ajou University. The population is adult men and women over the age of 19 living nationwide in Korea, and the sampling frame is a master panel held by Hankook Research, a specialized research organization, with more than 760,000 people. The sampling method utilized a proportional representation sampling method that varies by region, gender, and age. The survey methodology was a web survey via mobile phone and email, and the survey period was conducted from May 30 to June 3, 2022. Data was collected from 1571 people, with a maximum margin of sampling error of ±2.5 percentage points at the 95% confidence level, assuming random sampling. To analyze the determinants of energy saving behavior, the study executed regression analysis. To checked moderation effects by cost and opportunity, it examined interaction effects. Results: The results showed that respect for life, hedonic value, openness to change, attitudes, norms, and sense of control had significant effects on energy saving behavior, while selfish and altruistic values, hedonic value, openness to change, norms, and attitudes had effects on policy participation related with energy saving. In addition, the moderation effect analysis revealed six interaction effects, of which opportunity and cost were variables moderating effect of biospheric value on policy participation and attitude on policy participation. Conclusions: Based on the above findings, the research implications are as follows. First, we confirm the multidimensionality of energy saving behavior in that that the variables explaining energy saving behavior are not consistent from a theoretical perspective. Second, we verified that opportunities and costs that individuals face have an effect through interactions with variables that do not significantly explain behavior.
Keywords: behavior; cost; energy conservation; opportunity; policy engagement